Hypothermia on admission to a neonatal intensive care unit in Oromia, western Ethiopia: a case-control study - Tariku Tesfaye Bekuma; Bikila Regassa Feyisa; Belachew Etana Tolessa; Bikila Girma (BMJ Publishing Group, 2021)
Objective Hypothermia is believed to affect more than half of Ethiopian neonates. The goal of this study is to determine risk factors for newborn hypothermia in neonates admitted to public hospitals in the east Wollega zone of western Ethiopia's neonatal intensive care unit.Design Unmatched case-control study using neonates admitted to the intensive care unit.Setting Neonatal intensive care units at public hospitals in western Ethiopia.Patients Neonates admitted to intensive care units.Main outcomes The cases were all neonates with hypothermia (less than 36.5°C) and the controls were all neonates with a body temperature of greater or equal to 36.5°C when admitted to the neonatal intensive care unit for other reasons.Results The study involved the participation of 73 cases and 146 controls. The study found that delayed breastfeeding initiation after 1 hour (adjusted OR (AOR)=3.72; 95% CI: 1.39 to 10.00), admission weight less than 2500 g (AOR=3.43; 95% CI: 1.18 to 9.97), cardiopulmonary resuscitation at birth (AOR=3.42; 95% CI: 1.16 to 10.10.08), lack of immediate skin-to-skin contact with their mother (AOR=4.54; 95% CI: 1.75 to 11.81), night-time delivery (AOR=6.63; 95% CI: 2.23 to 19.77) and not wearing a cap (AOR=2.98; 95% CI: 1.09 to 8.15) were all associated with newborn hypothermia.Conclusions Neonatal hypothermia was associated with obstetric, neonatal and healthcare provider factors. As a result, special consideration should be given to the thermal care of low birthweight neonates and the implementation of warm-chain principles with low-cost thermal protection in Ethiopian public health facilities.